The Role of Destination Brand Love in Mediating Destination Brand Authenticity on Destination Loyalty - Nasrul, Nasrul; Rommy, Nursaban; Hapsari, Indri; Jurumai, La Pande; Roslan, Astil Harli (Jurnal Manajemen Industri dan Logistik, 2023)
This study aimed  to examine the role of destination brand love in mediating destination brand authenticity on destination loyalty (a study of marine tourists in Wakatobi National Park). The study  on destination brands is  important for several reasons, firstly, there are still limited studies on destination brand love as a mediation of destination brand authenticity to the destination loyalty. There were four hypotheses  developed and tested within 100 travelers as sample frame. Respondent data were collected from 100 tourists from Wakatobi National Park through questionnaires. Partial Least Square Data Analysis Technique (PLS) was used as a data analysis technique in this study. The results of this study showed  that the path of destination brand love can mediate destination brand authenticity on destination loyalty and the hypothesis was accepted in this study.